Selective Extraction of Transition Metals from Spent LiNixCoyMn1−x−yO2 Cathode via Regulation of Coordination Environment - Chang, Xin; Fan, Min; Gu, Chao‐Fan; He, Wei‐Huan; Meng, Qinghai; Wan, Li‐Jun; Guo, Yu‐Guo (Angewandte Chemie International Edition, 2022)
The complexity of chemical compounds in lithium‐ion batteries (LIBs) results in great difficulties in the extraction of multiple transition metals, which have similar physicochemical characteristics. Here, we propose a novel strategy for selective extraction of nickel, cobalt, and manganese from spent LiNixCoyMn1−x−yO2 (NCM) cathode through the regulation of coordination environment. Depending on adjusting the composition of ligand in transition metal complexes, a tandem leaching and separation system is designed and finally enables nickel, cobalt, and manganese to enrich in the form of NiO, Co3O4, and Mn3O4 with high recovery yields of 99.1 %, 95.1 %, and 95.3 %, respectively. We further confirm that the combination of different transition metals with well‐designed ligands is the key to good selectivity. Through our work, fine‐tuning the coordination environment of metal ions is proved to have great prospects in the battery recycling industry. The deep eutectic solvent composed of choline chloride and oxalic acid was prepared. After leaching at 120 °C for 10 hours, the nickel oxalate dihydrate and the filtrate containing other metal elements are separated. Then the filtrate is diluted with water to precipitate the cobalt oxalate dihydrate. Finally, manganese compounds were separated by adjusting pH.